Primary endosymbiosis and the evolution of light and oxygen sensing in photosynthetic eukaryotes - Rockwell, Nathan C.; Lagarias, J. C.; Bhattacharya, Debashish (Frontiers in Ecology and Evolution, 2014)
The origin of the photosynthetic organelle in eukaryotes, the plastid, changed forever the evolutionary trajectory of life on our planet. Plastids are highly specialized compartments derived from a putative single cyanobacterial primary endosymbiosis that occurred in the common ancestor of the supergroup Archaeplastida that comprises the Viridiplantae (green algae and plants), red algae, and glaucophyte algae. These lineages include critical primary producers of freshwater and terrestrial ecosystems, progenitors of which provided plastids through secondary endosymbiosis to other algae such as diatoms and dinoflagellates that are critical to marine ecosystems. Despite its broad importance and the success of algal and plant lineages, the phagotrophic origin of the plastid imposed an interesting challenge on the predatory eukaryotic ancestor of the Archaeplastida. By engulfing an oxygenic photosynthetic cell, the host lineage imposed an oxidative stress upon itself in the presence of light. Adaptations to meet this challenge were thus likely to have occurred early on during the transition from a predatory phagotroph to an obligate phototroph (or mixotroph). Modern algae have recently been shown to employ linear tetrapyrroles (bilins) to respond to oxidative stress under high light. Here we explore the early events in plastid evolution and the possible ancient roles of bilins in responding to light and oxygen.